Temperature and Nutrient Limitations Decrease Transfer of Conjugative IncP-1 Plasmid pKJK5 to Wild Escherichia coli Strains - Pallares-Vega, Rebeca; Macedo, Gonçalo; Brouwer, Michael S. M.; Hernandez Leal, Lucia; van der Maas, Peter; van Loosdrecht, Mark C. M.; Weissbrodt, David G.; Heederik, Dick; Mevius, Dik; Schmitt, Heike (Frontiers in Microbiology, 2021)
Plasmid-mediated dissemination of antibiotic resistance among fecal Enterobacteriaceae in natural ecosystems may contribute to the persistence of antibiotic resistance genes in anthropogenically-impacted environments. Plasmid transfer frequencies measured under laboratory conditions might lead to overestimation of plasmid transfer potential in natural ecosystems. This study assessed differences in the conjugative transfer of an IncP-1 (pKJK5) plasmid to three natural E. coli strains carrying extended-spectrum beta-lactamases, by filter mating. Matings were performed under optimal laboratory conditions (rich LB medium and 37 °C) and environmentally relevant temperatures (25, 15 and 9 °C) or nutrient regimes mimicking environmental conditions and limitations (synthetic wastewater and soil extract). Under optimal nutrient conditions and temperature, two recipients yielded high transfer frequencies (5 x 10-1) while the conjugation frequency of the third strain was 1000-fold lower. Decreasing mating temperatures to psychrophilic ranges led to lower transfer frequencies, albeit all three strains conjugated under all the tested temperatures. Low nutritive media caused significant decreases in transconjugants (-3 logs for synthetic wastewater; -6 logs for soil extract), where only one of the strains was able to produce detectable transconjugants. Collectively, this study highlights that despite less-than-optimal conditions, fecal organisms may transfer plasmids in the environment, but the transfer of pKJK5between microorganisms is limited mainly by low nutrient conditions.